2017
DOI: 10.1371/journal.pone.0187852
|View full text |Cite
|
Sign up to set email alerts
|

The abundance of health-associated bacteria is altered in PAH polluted soils—Implications for health in urban areas?

Abstract: Long-term exposure to polyaromatic hydrocarbons (PAHs) has been connected to chronic human health disorders. It is also well-known that i) PAH contamination alters soil bacterial communities, ii) human microbiome is associated with environmental microbiome, and iii) alteration in the abundance of members in several bacterial phyla is associated with adverse or beneficial human health effects. We hypothesized that soil pollution by PAHs altered soil bacterial communities that had known associations with human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 86 publications
(90 reference statements)
4
23
0
1
Order By: Relevance
“…Our results thus indicated that urban inhabitants were exposed to less diverse environmental microbiota and to potentially pathogenic bacteria at the same time. Moreover, as reported in our previous study (Parajuli et al, 2017 ), environmental pollutants such as polyaromatic hydrocarbons (PAH) can change bacterial communities in an urban context. Therefore, our findings suggest that anthropogenic disturbances are responsible for the difference in microbial community composition between rural and urban settings.…”
Section: Discussionmentioning
confidence: 56%
“…Our results thus indicated that urban inhabitants were exposed to less diverse environmental microbiota and to potentially pathogenic bacteria at the same time. Moreover, as reported in our previous study (Parajuli et al, 2017 ), environmental pollutants such as polyaromatic hydrocarbons (PAH) can change bacterial communities in an urban context. Therefore, our findings suggest that anthropogenic disturbances are responsible for the difference in microbial community composition between rural and urban settings.…”
Section: Discussionmentioning
confidence: 56%
“…It comprises the majority of Gram-negative bacteria, morphologically, physiologically and metabolically largely diversified [57,58], including phototrophs, heterotrophs, and chemolithotrophs, as well as numerous pathogens for humans, animals, and plants [59]. Its dominance was reported in soil contaminated by polyaromatic hydrocarbons (PAHs) [60,61] and oil [59]. In this study, its low abundance (15.06%) was observed in Ni-treated samples.…”
Section: Taxonomic Compositionmentioning
confidence: 65%
“…Soils including composted gardening materials host especially diverse microbial communities (Yu et al, 2015) and thus increasing contact with such soils for urban citizens could provide a means for increasing the diversity of their microbiota and further decrease the prevalence of asthma and atopies (von Hertzen & Haahtela, 2006). This is especially significant in the light of our earlier findings, which suggest that urbanization and pollution could lead to changes in soil microbiota and urbanization reduces microbial transfer indoors (Parajuli et al, 2017(Parajuli et al, , 2018.…”
mentioning
confidence: 64%